PENGEMBANGAN METODE ANALISIS BENZENA, TOLUENA, DAN XYLENA DALAM UDARA LINGKUNGAN KERJA MENGGUNAKAN IN HOUSE METODE DI PT UNILAB PERDANA - Rendi Maulana; Rofiq Sunaryanto; Charles Situmorang (JURNAL TECHLINK, 2020)
Benzene, Toluene and Xylene (BTX) compounds are compounds that have colorless and flammable characteristics, have a sweet odor with a low toxicity level, and are not soluble in water. This compound is often used as a solvent, extractor and as a chemical intermediary. The testing of BTX parameters in the working environment refers to the National Institute of Occupational Safety and Health (NIOSH) method number 1501. The method must be modified or developed in terms of equipment and instruments, due to looking at the condition of the materials and equipment in PT UP, i.e. using different columns, capillary columns, fused silica, 30m x 0.32-mm ID; 1-μm film 100% PEG becomes a Rtx-5MS column, and measurements using a FID detector become a Mass Spectrometer detector. And the solvent used is Carbon Disulfiida (CS2) to Methanol for gas chromatography. CS2 solvents are carcinogenic in the body so that they are harmful to human health. Besides being harmful to health, the waste produced by CS2 causes damage to the ozone layer on the earth's surface so that it can trigger global warming which will make the earth feel hot. In addition, CS2 solvents in Indonesia have begun to be reduced in production and will be illegal inthe future. Therefore, this method needs to be validated before doing a routine analysis so that the data obtained is valid.